A survey of face recognition techniques (2007)
A review of face recognition techniques has been carried out.Face recongition has been an attractive field in the society of both biological and computer vision of research. It exhibits the characteristics of being natural and low-intrusive. In this paper, an updated survey of techniques for face recognition is made. Methods of face regonition , such as geometric, statistical and neural networks approaches are presented and analyzed. The comparative performance of the variaous approaches is discussed.